Ethical identification of Muslim women on Mandangin Island: An ethnographic study - Anas Ahmadi (Masyarakat, Kebudayaan dan Politik, 2021)
In a community, ethics have a connection with religion. A person whose religion is vital would respect the ethics associated with that religion. Along with the current technology development, community ethics have begun to change, whether quickly or slowly. In a community, this change of ethics happens because it follows the development within modernism and globalization. This study explores the ethical identification of Muslim women in Mandangin Island, Madura Island, East Java. This study uses an ethnographic method that refers to Spradley’s. Data obtained from interviews with female informants who are categorized: adolescents, mothers, and grandmothers. Based on this research data, it is known that there are three ethics of Muslim women in Mandangin Island. First, they uphold ethics, who into this group (from young to old) do not want to ride a motorbike and wear jeans that are respected on and off the island. Second, those who carry out an ethical transformation, in this group, they (teenagers) adhere to manners while on Mandangin Island; however, they ride motorbikes and wear jeans outside the island. On the one hand, those who fall into this category want to appreciate and uphold ethics in the people of Mandangin Island and want to follow modernism. They want to be able to ride motorbikes and wear jeans like most women. Third, those who violate ethics. It is most unusual for the third category because Muslim women consider themselves to adhere to religion and ethics.